Dirichlet Averages of Generalized Multi-index Mittag-Leffler Functions - Saxena, R.K.; Pogany, T.K.; Ram, J.; Daiya, J. (Armenian Journal of Mathematics, 2011)
The object of this article is to investigate the Dirichlet averages of the generalized multi–index Mittag–Leffler functions introduced by Saxena and Nishimoto 23, 24. Representations of such relations are obtained in terms of Riemann–Liouville integrals and hypergeometric functions of several variables. Some interesting special cases of the established results associated with generalized Mittag–Leffler functions due to Srivastava and Tomovski 28 and multi–index Mittag–Leffler functions due to Kiryakova 13 are deduced. Certain results given earlier by Kilbas et al. 9 also follow as special cases of our findings.